Budaya Populer: Representasi dalam Film “My Generation” Karya Upi Aviyanto (Faculty of Communications Science, Dr. Soetomo University, 2019)
As time goes by, culture society has changes in generation from the past time to the present. So, each generation has their own habits and characteristics in it's time.